(untitled) (ModaPalavra e-periódico, 2024)
In this text, we investigate intersections between fashion, emotions, consumption, and performance from media materials collected about the life of Elke Maravilha. German, she arrived in Brazil at the age of six and had a meteoric career, from runway fashion shows to television. A celebrity established in the media scene, Elke drew attention on the runways for her unique style and the way she presented herself in fashion shows. On TV, she was a judge on talent shows and had her own talkshow. The article is methodologically oriented by cartographic studies. We produced, from the constituent sensibilities of Walter Benjamin’s cartographies, four constellations: 1) I want to draw attention; 2) Dionysian priestess; 3) necklace of wonders; 4) Elke in the artificial land. By investigating Elke’s aesthetic and performative dimension, we understand that the way clothes and props were used enabled an elaboration of the self and communicative expression.